Comparison of autocorrelation between CV-RISK independent variables in groups with and without history of cardiovascular diseases - Goutama, Ivany Lestari; ., Hendsun; Firmansyah, Yohanes; Su, Ernawati (International Journal of Advances in Medicine, 2020)
Background: Cardiovascular relative risk (CVRISK) is the latest cardiovascular relative risk score to evaluate the magnitude of cardiovascular risk in healthy people regardless of age and cardiovascular risk severity. The aim of the study is to determine the correlation between each independent variables of CVRISK score in individuals with and without history of cardiovascular diseases (CVD). Methods: The study design is cross-sectional study. We conducted it online through social media using Google forms from June to August 2020. Participants include all productive age groups from 16 to 60 years. The data were processed using excel and statistically tested. Descriptive data analysis uses tabulated data which is displayed in numbers or proportions (categorical) and single data distribution (numeric). Statistical association analysis uses the categorical-correlation test with 2 statistical tests that use eta on nominal-ordinal variables and contingency coefficients on nominal-nominal variables. Results: There is a strong autocorrelation between hypertension and high tryglyceride levels (p value 0.001; correlation 0.549; risks 30.14%), nutritional status and low-density lipoprotein cholesterol (LDL-C) levels in CVD group (p value 0.002; correlation 0.774; risks 59.90%) and non-CVD group (p value 0.000; correlation 0.757; risks 57.3%). Hypertension and risky LDL-C levels firmly proves a very strong correlations and significant relationship in CVD groups (p value 0.014; correlation 0.947; risks 89.68%). Conclusions: There is a correlation that varies from weak to very strong among the independent variables in the CVRISK scoring of the participants. Further research is needed to determine the potentiality of CVRISK as an early prevention in determining the cardiovascular risk of individuals with and without history of CVD.